Prevalence and associated risk factors of Pseudomonas aeruginosa infection in Diabetic wounds in Duhok province, Iraq - Marwa S. Ibrahim; Ibrahim A. Naqid (PLoS ONE, 2026)
Background and aims Diabetes mellitus is a chronic metabolic disorder and a major global health problem, predisposing patients to wound infections, with Pseudomonas aeruginosa being a frequent and resistant pathogen. This study aimed to identify P. aeruginosa , assess associated risk factors, and determine its antibiotic susceptibility pattern in diabetic wound infections in Duhok Province, Kurdistan Region, Iraq. Methods This cross-sectional study was conducted from June 2024 to July 2025 in Duhok Province, Kurdistan Region, Iraq. A total of 141 wound swab samples were collected from diabetic patients aged ≥18 years. P. aeruginosa was identified using biochemical tests, Vitek®2, and 16S rDNA PCR. Antimicrobial susceptibility testing was performed by the disc diffusion method on Mueller–Hinton agar, and data were analyzed using GraphPad Prism software. Results Out of 141 wound infection samples collected from diabetic patients, P. aeruginosa was isolated in 44.68% of cases. Overall, sociodemographic factors showed no significant association with PsA infection, except for occupational status in the multivariable analysis 0.12 [0.02–0.97, p = 0.046] and overweight 0.29 [0.10–0.82, p = 0.019]. Clinically, most variables including HbA1c, duration of diabetes, comorbidities, treatment type, and wound characteristics were not significantly associated with PsA infection. The only significant predictor was wound location, with leg-region infections showing a higher risk of PsA 3.94 [1.24–12.5, p = 0.02]. P. aeruginosa isolates showed high levels of multidrug resistance, especially to aztreonam, ceftazidime, cefepime, and tobramycin. Colistin showed the lowest resistance and highest sensitivity, followed by relatively better susceptibility to carbapenems. Conclusion P. aeruginosa is a common cause of wound infections in patients with diabetes mellitus, with its prevalence significantly associated with body mass index, occupational status and wound location, with leg-region wounds showing a higher risk. P. aeruginosa isolates demonstrated high multidrug resistance, although colistin and carbapenems retained relatively better activity. Early detection and appropriate antibiotic selection are essential to reduce complications and improve patient outcomes.